The effect of 20 minutes of cool running water first aid within three hours of thermal burn injury on patient outcomes: A systematic review and meta-analysis. (December 2022) - Griffin, Bronwyn; Cabilan, C.J.; Ayoub, Bassel; Xu, Hui (Grace); Palmieri, Tina; Kimble, Roy; Singer, Yvonne
Abstract: Background: Burn injuries are a leading cause of morbidity that can result in devastating disability and poor quality of life for survivors. This systematic review aimed to synthesise evidence regarding the effect of 20 minutes of cool running water (CRW) within three hours of injury on outcomes of patients with thermal burn injuries. Methods: This systematic review was conducted in reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Multiple databases (PubMed, EMBASE, CENTRAL, CINAHL Complete via EBSCO, PROQUEST Dissertations and Theses), and the Australia New Zealand Clinical Trial Registry were searched for eligible studies published in English and Chinese, without date restriction. Meta-analyses were undertaken Methodological quality of studies was assessed by using Downs and Black Checklist. Results: Of 323 records, seven studies were included. The majority (67%) of studies were conducted in Australia and New Zealand. The methodological quality was ranked between 'fair' and 'good'. Twenty minutes of CRW within the first three hours of burn injury significantly decreased the odds of patients requiring skin grafting and surgical intervention for wound management. Conclusions: There is considerable evidence suggesting the application of 20 min of CRW within the first three hours of injury improves outcomes for patients with burn injury. Consensus between burn organisations and collaborative efforts to translate evidence into practice are needed to optimise burn first aid care which can improve patient outcomes globally.